2013
DOI: 10.1504/ijdmb.2013.055499
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating data mining algorithms using molecular dynamics trajectories

Abstract: Molecular dynamics simulations provide a sample of a molecule's conformational space. Experiments on the mus time scale, resulting in large amounts of data, are nowadays routine. Data mining techniques such as classification provide a way to analyse such data. In this work, we evaluate and compare several classification algorithms using three data sets which resulted from computer simulations, of a potential enzyme mimetic biomolecule. We evaluated 65 classifiers available in the well-known data mining toolkit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…It was reported that by applying 179 classifiers on 121 datasets from the UCI database, the RF classifier versions produced the best results in most of the cases [21]. A similar conclusion was also derived for smaller scale investigation with 65 WEKA classifies on 3 datasets [22]. In our case, the basic RF classifiers even slightly outperformed the Auto-WEKA classifier with RF in its core (98.6 vs. 97.1%).…”
Section: Resultssupporting
confidence: 85%
“…It was reported that by applying 179 classifiers on 121 datasets from the UCI database, the RF classifier versions produced the best results in most of the cases [21]. A similar conclusion was also derived for smaller scale investigation with 65 WEKA classifies on 3 datasets [22]. In our case, the basic RF classifiers even slightly outperformed the Auto-WEKA classifier with RF in its core (98.6 vs. 97.1%).…”
Section: Resultssupporting
confidence: 85%
“…Agreeing with information from the literature periodical, various data mining techniques are used for HDP with higher accuracy and fewer error rates [8]. Different types of studies have been conducted to target the prediction of HD, which includes the following related work: A framework for HDP named An Effective Classification Rule Technique for Heart Disease Prediction has been recommended by Vijayarani et al [9].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In other words, the Random Committee Algorithm creates a group of base classifiers and averages their predictions. Each base classifier is based on the same data, however uses several numbers of random seed [31]. This is clear only if the base classifier is chosen at random; on the other hand, all classifiers would be the same.…”
Section: Random Committee Algorithmmentioning
confidence: 99%